Relationship between Cultural Dimensions and Professional Identity among Prospective Teachers at University of Education Lahore - Sumaira Majeed; Muhammad Aslam; Rizwan Ahmad (JCTE, 2026)
The intent of the study was to explore the correlation between cultural dimension and professional identity of prospective teachers. The researchers have the expectation that study might help for prospective teacher to develop their professional identity. The population of the study were the prospective teachers’ enrolled in University of Education. Total 400 students enrolled in different campuses of University of Education participated in the research selected through random sampling. A detailed questionnaire was adapted for cultural dimensions and professional identity and it was comprised of 57 items. The validity of the instrument was ensured with the opinion of expert and necessary changes were made. Pilot testing was conducted to ensure the reliability of the cultural dimension scale and professional identity scale. The research correlational research and cross-sectional survey was employed. The data of this study was analyzed through SPSS and different necessary techniques of statistics were used. Pearson correlation coefficient (Pearson r) was applied to find the correlation among prospective teachers’ cultural dimension and professional identity and t[1]test was applied to find the difference among prospective teachers’ cultural dimension and professional identity on the basis of gender. Positive correlation between prospective teacher’s cultural orientation and professional identity was found and findings of this research were confirmed through regression analysis.